SISTEMA ESPECIALISTA PARA TELEDIAGNÓSTICO NO AMBIENTE DE WEB SERVICES WST Web Services Telediagnosis - Luna Filho, Antonio Luis do Rêgo (2005)
This work approaches the telemedicine through an area of study about telediagnosis. The solution proposed here will be the development of an expert system which has the objective of sharing rule base in an internet environment, using the web services technology. The knowledge basis of expert system will be built on malaria diseases. Some technologies such as: the JESS - Java Expert System Shell, the Java language and also Protegé tool to ontologies generations. The major interest of this project is to attend communities located far from cities giving them accurate medical support.